Diagnostics of femoral head status in humans using laser spectroscopy – In vitro studies. Issue 10 (23rd December 2016) - Lin, Huiying; Li, Wansha; Zhang, Hao; Chen, Peng; Chen, Delong; He, Wei; Svanberg, Sune; Svanberg, Katarina
Abstract : Osteonecrosis of the femoral head (ONFH), a recalcitrant and disabling disease, is caused by inadequate or fully disrupted blood supply to the affected segment of the subchondral bone. Theoretically, there will develop gas‐filled pores during the bone decay process due to lacking blood supply. Unfortunately, the relationship between the gas‐filled pores and ONFH is still unclear. Here, we have introduced diode laser absorption spectroscopy to detect oxygen and water vapor signals in the femoral heads from hip replacement in 19 patients. Five samples are affected by osteoarthritis (OA) and the others are related to ONFH. Oxygen and water vapor signals could be obtained, demonstrating the presence of gas‐filled pores in both the OA and ONFH groups while the measurement results showed no significant difference. A study of gas exchange was also performed on one excised bone sample to study how these gas pores communicate with the ambient air. The results suggested that the obtained oxygen signals inside the bone samples originate from the invasion of ambient air, which is not expected in vivo . In conclusion, the ability to detect the gas signal of laser absorption spectroscopy shows the potential for the medical application of assessing the human femoral head in vivo . Abstract : Second derivative of water vapor absorption signal recorded from the interior of a human femoral head sample, demonstrating the presence of gas‐filled pores indicating osteonecrosis. The recording was made by diode‐laser spectroscopy.